MLVA for Salmonella enterica subsp. enterica Serovar Dublin: Development of a Method Suitable for Inter-Laboratory Surveillance and Application in the Context of a Raw Milk Cheese Outbreak in France in 2012 - Vignaud, Marie-Léone; Cherchame, Emeline; Marault, Muriel; Chaing, Emilie; Le Hello, Simon; Michel, Valerie; Jourdan-Da Silva, Nathalie; Lailler, Renaud; Brisabois, Anne; Cadel-Six, Sabrina (Frontiers in Microbiology, 2017)
Salmonella enterica subspecies enterica serovar Dublin (S.Dublin) may affect production and animal health principally in cattle herds with consequent important economic losses. This serovar figures between the 9th and 16th rank among the most frequently serovars isolated in human since 2000 in France and the resulting outbreaks commonly persist several months due to its pathogenicity. Today, given that, the gold standard method, PFGE usually used to sub-type food pathogen and trace sources of contamination, provides insufficient discrimination for epidemiological investigations, we propose in this study a standard operating procedure for multiple-locus variable-number tandem repeat analysis (MLVA) of S. Dublin. The scheme developed here is based on six loci of variable number of tandem repeats (VNTRs) and was evaluated on 401 strains isolated from animals, food and human sources. A reference set of twenty-four strains is provided to harmonize MLVA results and allow data exchanges between laboratories. Among the panel of studied strains, nineteen were isolated from a raw milk cheese outbreak that occurred in France during several months in 2012. The analysis of this outbreak aims to explore in vivo the stability of the six chosen VNTRs and demonstrated the high discrimination power of this developed scheme. This original MLVA protocol could be easily and routinely carried out for serovar Dublin isolates monitoring and outbreak investigations conducting.